ANALISIS JARINGAN PADA JEJARING AKTOR DALAM MENGEMBANGKAN POTENSI WISATA DI DESA BANJARSARI KECAMATAN PANGALENGAN - Guruh Ramdhan Hasbillah Syam; Indra Aditya; Dewi Noor Azijah (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This study aims to analyze the structure of actor networks in the development of tourism destinations in Banjarsari Village, focusing on how interactions between actors influence tourism management strategies. To facilitate the analysis of these networks in enhancing tourism potential, the research adopts a case study design with qualitative methods. Through this approach, the study examines the relationships formed between actors in the tourism development process in depth. The research applies Actor Network Theory (ANT), introduced by Bruno Latour and John Law emphasizing the network dimension. This framework is expected to provide deeper insights into the factors that either support or hinder tourism management based on actor networks. The networks that emerge among actors in developing Banjarsari Village’s tourism potential exhibit three key characteristics: communal value based networks, direct communication networks, and tourism synergy networks. The communal value-based network is shaped by strong local values of mutual cooperation and solidarity, acting as a social adhesive despite the absence of formal structures. The direct communication network emerges due to the fac to face interactions among actors, facilitated through deliberations and direct visits. Finally, the tourism synergy network reflects the collaborative nature of various tourism attractions within Banjarsari Village, where destinations complement rather than compete with each other.